2007
DOI: 10.1154/1.2754715
|View full text |Cite
|
Sign up to set email alerts
|

Structural refinement of neutron powder diffraction data of two-stage martensitic phase transformations in Ti50.75Ni47.75Fe1.50 shape memory alloy

Abstract: Transformation behaviors of the technologically important polycrystalline Ti 50.75 Ni 47.75 Fe 1.50 shape memory alloy were investigated using differential scanning calorimeter ͑DSC͒ and powder diffraction techniques. DSC revealed that there are two-stage ͑i.e., cubic→ trigonal→ monoclinic͒ martensitic phase transformations on cooling and a one-step transformation ͑monoclinic→ cubic͒ on heating.In situ structural refinement of cubic→ trigonal→ monoclinic on cooling was carried out using the D1A high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The refined structure parameters for the trigonal phase agreed reasonably well with the results reported by Sitepu (2007), and the Ni 4 Ti 3 precipitate phase in the aged (850 °C, 24 h) Ni-rich Ni 50.7 Ti 49.30 SMA also agreed quite well with the single-crystal results of Tirry et al (2006) (Table III). The concentrations of trigonal and precipitate phases are 93% and 7% at room temperature.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The refined structure parameters for the trigonal phase agreed reasonably well with the results reported by Sitepu (2007), and the Ni 4 Ti 3 precipitate phase in the aged (850 °C, 24 h) Ni-rich Ni 50.7 Ti 49.30 SMA also agreed quite well with the single-crystal results of Tirry et al (2006) (Table III). The concentrations of trigonal and precipitate phases are 93% and 7% at room temperature.…”
Section: Resultssupporting
confidence: 88%
“…No significant improvement in the figures-of-merit [ R P , R W P , R ( F 2 )] and goodness-of-fit index ( χ 2 ) were found when the inversion center was removed from the P 3¯ model, suggesting that the space group of trigonal structure in Ti 50.75 Ni 47.75 Fe 1.50 alloy at room temperature, on cooling, was indeed P 3¯ and not lower symmetry P 3 or P 31 m . Sitepu (2003, 2007) showed that (i) the refined atomic parameters for all synchrotron diffraction data sets of trigonal phase converged only when the P 3¯ space group was used in the Rietveld refinement and (ii) a combined neutron and synchrotron refinement confirmed that P 3¯ is the correct space group for the trigonal phase. While the texture index for the trigonal phase is 1.136, the corresponding value for the precipitate is 1.216 which agrees reasonable with the cubic phase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations